DISEÑO DE UNA TAREA FENOMENOLÓGICA PARA LA EXPLORACIÓN DEDUCTIVA DE LA REGLA DE LA CADENA EN VARIAS VARIABLES - Muñoz Ortiz, Eduardo Emiliano (2026)
In this document a route for the design of a mathematical phenomenological task is presented. For exemplify, we make an analysis of its implementation, in the context of the course MA-1022 Cálculo para Ciencias Económicas II focused on the chain rule in several variables. Our theoretical background is the Design Thinking methodology, considering the theory of Carroll's Learning Scenarios and based on Matos's Design Principles. With the design of the problem proposed in the task, we sought to achieve a better understanding of hierarchy and the relationships between the variables involved, which favored the consolidation of the procept associated with the chain rule theorem in several variables according to Tall. As the task provided a context close to the disciplinary area, it allowed students to identify the composition of functions in several variables and to make sense of the tree diagram of dependencies between variables, useful in the application of the theorem.